PENDAFTARAN PERALIHAN TANAH NEGARA MENJADI TANAH HAK MILIK BERDASAR PP NOMOR 24 TAHUN 1997 TENTANG PENDAFTARAN TANAH - Jabaruddin Jabaruddin (Jurnal Akrab Juara, 2018)
The application must meet the established requirements and through the process of inspection in accordance with applicable laws and regulations, subsequent to the issuance of a Decision on the granting of a Property or a decision of rejection submitted to the applicant by registered mail or in any other manner ensuring that the decision is reached to the applicant. Issuance of a Decree on the Provision of Property that serves as a proof of ownership that a person or a legal entity acquires the right to a plot of land and the basis or basis of the right of recognition of a State to a person or legal entity over a plot of land under its control. Keywords: Registration, Transition, Land, Rights, Owned